Risk of Venous Thromboembolism Recurrence: High Negative Predictive Value of D-dimer Performed after Oral Anticoagulation Is Stopped - Palareti, Gualtiero; Legnani, Cristina; Cosmi, Benilde; Guazzaloca, Giuliana; Pancani, Claudia; Coccheri, Sergio (Thrombosis and Haemostasis, 2002)
In some patients with previous venous thromboembolism (VTE) D-dimer levels (D-Dimer) tend to increase after oral anticoagulant therapy (OAT) is stopped. The aim of our study was to evaluate the predictive value of D-Dimer for the risk of VTE recurrence after OAT withdrawal. After a first episode of deep vein thrombosis (DVT) of the lower limbs and/or pulmonary embolism (PE), 396 patients (median age 67 years, 198 males) were followed from the day of OAT discontinuation for 21 months. D-dimer was measured on the day of OAT withdrawal (T1), 3-4 weeks (T2) and 3 months (+/− 10 days, T3) thereafter. The main outcome events of the study were: objectively documented recurrent DVT and/or PE. D-dimer was found to be increased in 15.5%, 40.3% and 46.2% of the patients at T1, T2 and T3, respectively. In 199 (50.2%) patients, D-dimer levels were elevated in at least one measurement. During a follow-up of 628.4 years, 40 recurrences were recorded (10.1% of patients; 6.4% patient-years of follow-up). D-dimer was increased in at least one measurement in 28 of these cases, but remained normal in 11 subjects (three of whom had recurrent events triggered by circumstantial factors, three with malignancyassociated factors) (in one subject D-dimer was not measured). The negative predictive value (NPV) of D-dimer was 95.6% (95% CI 91.6-98.1) at T3 and was even higher (96.7%; 95% CI 92.9-98.8) after exclusion of the six recurrences due to circumstantial factors. Only five idiopathic recurrences occurred in the 186 patients with consistently normal D-dimer. In conclusion, D-dimer has a high NPV for VTE recurrence when performed after OAT discontinuation.
Keywords: D-dimer; venous thromboembolism; recurrence; predictive value; DVT